2021
DOI: 10.1039/d1sc00564b
|View full text |Cite
|
Sign up to set email alerts
|

Broad-band spectroscopy of a vanadyl porphyrin: a model electronuclear spin qudit

Abstract: We show that a sizeable electronuclear entanglement of the S = 1/2 and I = 7/2 spins of a vanadyl porphyrin provides the conditions to act as a universal 4-qubit processor, and thus implement quantum error correction at the molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 53 publications
0
61
0
Order By: Relevance
“…Since the spin ensemble is driven without a resonant mode, it is also interesting to compare our technique with on‐chip single‐tone broadband MW spectroscopy. [ 65–68 ] In these latter experiments a single MW tone is injected into a coplanar or a microstrip transmission line (i.e., no resonant MW modes) and used as a probe tone, to monitor the variation of the transmission induced by the ensemble. Broadband transmission spectroscopy offers large tunability of the frequency (several gigahertz), which can be used to map the energy levels of the spin ensemble as a function of the static magnetic field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the spin ensemble is driven without a resonant mode, it is also interesting to compare our technique with on‐chip single‐tone broadband MW spectroscopy. [ 65–68 ] In these latter experiments a single MW tone is injected into a coplanar or a microstrip transmission line (i.e., no resonant MW modes) and used as a probe tone, to monitor the variation of the transmission induced by the ensemble. Broadband transmission spectroscopy offers large tunability of the frequency (several gigahertz), which can be used to map the energy levels of the spin ensemble as a function of the static magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Broadband transmission spectroscopy offers large tunability of the frequency (several gigahertz), which can be used to map the energy levels of the spin ensemble as a function of the static magnetic field. [ 65,68 ] In our two‐tone spectroscopy, the dispersive shift of the cavity scales as the inverse of the detuning with respect to the probing cavity mode (Equation (3)), giving a lower tunability for the drive frequency. However, the dispersive shift depends also by the coupling rate providing that an optimal working point can be found in the tradeoff between detuning and magnetic coupling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it provides a large spin (I ¼ 7/2, eight levels) nuclear qudit, coupled by hyperne interaction to an electronic spin 1/2. Recent studies on the same 45,46 and very similar compounds 47 have reported remarkable electron spin coherence times, thus suggesting this system also as a very promising candidate qudit. However, to actually demonstrate this, we now need to focus on nuclear spin degrees of freedom.…”
Section: Introductionmentioning
confidence: 90%
“… 9 12 , 39 , 41 , 62 Recent studies further pointed out that in spite of the small quadrupole interaction typical of 51 V nucleus (and 3d metal ions in general), hyperfine coupling yields a pattern of levels which can be reproduced by an effective quadrupolar splitting along specific magnetic field directions. 63 This energy level structure gives full control of the system by radiofrequency (rf) pulses resonant with single-quantum transitions. 64…”
Section: Introductionmentioning
confidence: 99%